Pathohistological features and correlations between morphological indices of damage in the form of hematogenous osteomyelitis - Brodie abscess - V. V. Hryhorovskyi; M. P. Hrytsai; A. S. Hordii; O. B. Liutko; А. V. Hryhorovska (Zaporozhye State Medical University, 2017)
Research objective: On the basis of pathohistological research of the destructive form of hematogenous osteomyelitis with a latent course foci (Brodie's abscess) and performing of the grade-frequency analysis of the semi-quantitative indices reflecting features of the foci structure to find correlations between some morphological indices of a tissue condition in the damage foci. As research material fragments of the damaged tissues of the pathological foci of 25 patients with Brodie abscess (from 6 patients tissue material was received twice) served. By the localization of the foci distribution was the following: tibia - 24 cases, femur - 4, calcaneus - 2, clavicle -1. In total 31 histologic and semi-quantitative histomorphometric researches were performed, on the basis of morphological indices the grade-frequency and correlation analysis with association coefficient determination were carried out. Results. Brodie abscess - a variant of the destructive form of hematogenous osteomyelitis, has certain clinical and clinico-laboratory features, and the lesion foci - characteristic pathological changes. Particularly, average parameters of such clinico-laboratory indices as specific leukocytes number and a portion of stab leukocytes in the formula did not fall outside the limits of normal values. In most cases of Brodie abscess Staphylococcus aureus was seeded from tissues. The main pathomorphological changes at Brodie abscess involve capsule structures, necrotic and resorptive changes of spongiosa trabecules, features of productive-infiltrative and exudative inflammations in a focus capsule. The cases at which the internal membrane corresponds to a granulation tissue structure, exudative inflammation more often was of low activity, productive inflammation, on the contrary - more often was of high activity; in most cases within tissues small sequesters occur. Conclusions. Between some morphological indices of Brodie abscess foci tissue condition high significant (p<0.01) correlations which correspond to values of association coefficient in the range of values rа = 0.4-0.6 were found: "granulation tissue prevalence in the capsule " - "productive inflammation of high activity prevalence" - positive dependence, weak association; "granulation tissue prevalence in the capsule " - "presence of small sequesters" - positive dependence, weak association; "productive inflammation of high activity prevalence" - "presence of small sequesters" - dependence positive, moderate association.